Worshippers of the Gods Debating Paganism in the Fourth-Century Roman West - Gassman, Mattias 1990- (Oxford Oxford University Press USA - OSO, 2020)
Worshippers of the Gods shows how fourth-century Latin writers rethought traditional religion during Christianity's rise. Through five interlocking studies of inscriptions, laws, senatorial papers, and Christian polemics, it traces shifting conceptions of paganism from the Tetrarchic persecution, through Constantine's reign, to the 'disestablishment' of the Roman cults in the 380s.
cover -- Half Title -- Series -- Worshippers of the Gods -- Copyright -- Contents -- Acknowledgements -- List of Abbreviations -- Introduction -- 1. 'Like a Stream of Tullian Eloquence': Lactantius, Cicero, and the Critique of Roman Religion in the Divine Institutes -- 2. On the Error of Profane Religions: Emperors and Traditional Religion after Constantine -- 3. 'The Manifold Divinity of the Gods': 'Paganism' in Fourth-​Century Rome -- 4. Rome, Religion, and Christian Emperors: Rethinking the Altar of Victory Affair -- 5. Commemorating Vettius Agorius Praetextatus: Senators and Traditional Religion in 380s Rome -- Conclusion -- Bibliography -- Index.
Description based on publisher supplied metadata and other sources
Keywords: Christianity and other religions-Rome; Electronic books